Health-related quality of life of Korean older adults according to age, sex, and living arrangements: a cross-sectional study - Hwang, Horim A.; Jeong, Hyunsuk; Yim, Hyeon Woo (Frontiers in Public Health, 2023)
Introduction The number and proportion of older adults living alone is a significant issue. While the number of the oldest old people is also expected to increase, their health characteristics are poorly understood. This study aims to evaluate the health-related quality of life (HRQoL) of the oldest old people according to age, sex, and living arrangements. Methods This study is based on the Korea Community Health Survey 2021. Among the survey's 229,242 observations, 73,617 observations aged 65 or higher were used for the analysis. The study participants were divided into 5-year age intervals (from 65–69 to 90+), sex, and living arrangements. The outcome variables are the EuroQol 5 Dimensions (EQ-5D) index score and the problem reporting rates of the five dimensions of EQ-5D. Results The mean EQ-5D index scores were 0.896 at 65–69 and 0.741 at 90+. The mean EQ-5D index score decreased more rapidly as age increased. Women showed consistently lower mean EQ-5D index scores than men in all age intervals. The proportion of older adults living alone increased from 18.1% at 65–69 to 43.6% at 90+. The odds of reporting problems with anxiety/depression among older men living alone were estimated to be significantly higher than older men living with someone (aOR 1.22 95% CI 1.05–1.43). The odds of reporting problems in self-care and usual activity among older women living alone were estimated to be significantly lower than older women living with someone (aOR 0.88 95% CI 0.70–0.83 and aOR 0.88 95% CI 0.82–0.94) Conclusion This study showed that older adults' HRQoL deteriorates as their age increases. Moreover, living alone may lead to different effects on older adults' HRQoL according to sex. More comprehensive studies and collaborative attention are needed to identify and provide customized care for older adults.